Perancangan Sistem Manajemen Mutu ISO 9001:2015 di CV Indo Metal Forming - Alexander Prayogo Wibowo; Jani Rahardjo (Jurnal Titra, 2020)
Designing the documents are one step to design the Quality Management System (QMS) at CV Indo Metal Forming. Documents designed according the clause’s requirement of ISO 9011:2015. Beginning percentage of the fulfillment is 16,67% with average clause’s fulfillment is 12,07%. Set the vision and mission, quality policy, KPI, interested parties/stakeholders, company business process, SWOT analysis, risk identification, SOP, and others did to complete the requirement of ISO 9001:2015. Those documents increase the percentage of fulfillment to 83,33% with average clause’s fulfillment is 74,05%. The verified documents are going to implement based company activities. The purpose of implementation documents are develop and keep stability and consistency of quality management system. Documents must keep as company archieves and should reviewed as evaluation and development of quality management system.